Design Computing and Cognition '08 2008
DOI: 10.1007/978-1-4020-8728-8_20
|View full text |Cite
|
Sign up to set email alerts
|

Compound Analogical Design: Interaction between Problem Decomposition and Analogical Transfer in Biologically Inspired Design

Abstract: Biologically inspired design (BID) can be viewed as an example of analogy-based design. Existing models of analogy-based design do not fully account for the generation of complex solutions in BID, especially those which contain compound solutions. In this paper we develop a conceptual framework of compound analogical design that explains the generation of compound solutions in design through opportunistic interaction of two related processes: analogical transfer and problem decomposition. We apply this framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…Vattam et al [7] and Helms et al [8] studied the cognitive account of biomimetic design in the context of students working on projects in a biologically inspired design course. Helms et al reported a number of common errors made by designers, including solution fixation, misapplied analogy, and improper analogical transfer.…”
Section: Relevant Work In Biomimetic Designmentioning
confidence: 99%
“…Vattam et al [7] and Helms et al [8] studied the cognitive account of biomimetic design in the context of students working on projects in a biologically inspired design course. Helms et al reported a number of common errors made by designers, including solution fixation, misapplied analogy, and improper analogical transfer.…”
Section: Relevant Work In Biomimetic Designmentioning
confidence: 99%
“…In this paper, we first briefly summarize a finding from an earlier study of biologically inspired design that we conducted in Fall 2006 [22,38]. In the remainder of the paper, we describe in detail our current study of biologically inspired design conducted in Fall 2008.…”
Section: Studying Biologically Insipired Designmentioning
confidence: 99%
“…This understanding led the designers to decompose their original problem into two separate functions, one for slow and stealthy movement, and one for rapid, yet stealthy movement. Helms, Vattam & Goel [22] and Vattam, Helms & Goel [38] describe the initial study in detail. Team FORO, which included the first author of this paper, was composed of six team members including four undergraduates (two biology majors and two mechanical engineering majors) and two computer science graduate students.…”
Section: Summary Of An Initial Studymentioning
confidence: 99%
“…Vattam et al (2008) describe a complex interplay between problem decomposition and analogy retrieval and termed this process 'compound analogical design.' The authors note that multiple biological analogies could be used together to form a single design solution.…”
Section: Problem Definitionmentioning
confidence: 99%